2020
DOI: 10.1080/10095020.2020.1730712
|View full text |Cite
|
Sign up to set email alerts
|

Toward a unified theoretical framework for photogrammetry

Abstract: The objective of photogrammetry is to extract information from imagery. With the increasing interaction of sensing and computing technologies, the fundamentals of photogrammetry have undergone an evolutionary change in the past several decades. Numerous theoretical progresses and practical applications have been reported from traditionally different but related multiple disciplines, including computer vision, photogrammetry, computer graphics, pattern recognition, remote sensing and machine learning. This has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 59 publications
0
3
0
1
Order By: Relevance
“…Las nuevas tecnologías de visualización son de importancia primordial en la difusión del conocimiento. A pesar del potencial de visuali-zación, los académicos perciben la producción de imágenes digitales como una meta intermedia, el mayor desafío radica en crear nuevas herramientas que usan modelos 3D para ayudar a la investigación (Shan, 2020).…”
Section: Diagrama De Flujo De Trabajo De Impresión 3dunclassified
“…Las nuevas tecnologías de visualización son de importancia primordial en la difusión del conocimiento. A pesar del potencial de visuali-zación, los académicos perciben la producción de imágenes digitales como una meta intermedia, el mayor desafío radica en crear nuevas herramientas que usan modelos 3D para ayudar a la investigación (Shan, 2020).…”
Section: Diagrama De Flujo De Trabajo De Impresión 3dunclassified
“…Researchers in the photogrammetry community have proposed methodologies for incorporating semantic information in the photogrammetric pipeline [42][43][44][45]. Research works on improving photogrammetric tasks using semantic information have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Photogrammetric methods -since ever -aim to provide practical, reliable, and daily-based routines and solutions for geospatial data generation, geometric processing, and semantic interpretation -even with manual intervention to keep accuracy as high as possible. For two decades the community has provided many automated algorithms, also based on Artificial Intelligence (AI), to speed up geospatial data generation and interpretation, increase efficiency as well as robustness (Hartmann et al, 2015;Zhu et al, 2017;Becker et al, 2018;Gong and Ji, 2018;Yao et al, 2018;Liu et al, 2019;Griffiths and Boehm, 2019;Stathopoulou et al, 2019;Heipke and Rottensteiner, 2020;Huang et al, 2018;Shan et al, 2020;Chen et al, 2020a;Oezdemir et al, 2021;Qin and Gruen, 2021;Remondino et al, 2021). For sure there is still a hype around deep learning in research activities and in the media, but these methods are really a treasure trove for innovation in the geospatial field.…”
Section: Introductionmentioning
confidence: 99%